Assistance in the Preparation of Scientific Manuscripts Using Artificial Intelligence (AI) and Google Scholar to Enhance Students’ Academic Literacy and the Quality of Scholarly Writing - Rizki, Muhammad (⁠International Journal of Asia Pacific Community Service, 2025)
This community service program aims to enhance students’ academic literacy and scientific writing skills through the ethical and responsible use of Artificial Intelligence (AI) and Google Scholar. The activity involved 30 students from various study programs in a single implementation. The challenges faced by students include limited ability to identify reputable scholarly sources, organize scientific manuscripts systematically, and maintain originality and academic integrity. The program employed training, mentoring, and hands-on practice, focusing on effective literature search strategies using Google Scholar, the use of AI as a supportive tool in academic writing, and the application of proper citation and paraphrasing in accordance with scholarly standards. The activities were conducted through material presentations, interactive discussions, and evaluation of participants’ scientific writing outputs. The results indicate improvements in students’ ability to access relevant academic sources, develop well-structured manuscripts, and enhance awareness of academic ethics and integrity. Therefore, this program contributes to strengthening a high-quality academic culture that is adaptive to technological advancements in higher education.